PERFORMANCE EVALUATION OF RSUD H. ABDUL MANAP JAMBI USING THE BALANCED SCORECARD APPROACH: A FOUR-PERSPECTIVE ANALYSIS - Sari, Febriyani Nopa; Setiawati, Rike; Fitriaty (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to evaluate the performance of RSUD H. Abdul Manap Kota Jambi during the 2020–2023 period using the Balanced Scorecard approach, which consists of four key perspectives: financial, customer, internal business processes, and learning and growth. A descriptive quantitative method was employed, using secondary data from financial reports, hospital performance indicators, and survey data from patient and employee satisfaction questionnaires. From the financial perspective, the hospital demonstrated generally strong performance, with favorable liquidity and solvency ratios. However, activity ratios, particularly collection period and total asset turnover, indicated areas needing improvement. The customer perspective showed high patient retention and satisfactory service quality, although the hospital struggled to attract new patients, as reflected in the low acquisition rate. In terms of the internal business process perspective, performance was less optimal. Indicators such as Bed Occupancy Rate (BOR), Turn Over Interval (TOI), and Bed Turn Over (BTO) remained below ideal standards, suggesting inefficiencies in the use of inpatient facilities. Conversely, indicators like Average Length of Stay (AvLOS), Net Death Rate (NDR), and Gross Death Rate (GDR) met national healthcare benchmarks. The learning and growth perspective revealed positive outcomes, especially in employee retention and job satisfaction. Although training participation was relatively low, its consistent implementation each year reflected the hospital’s commitment to human resource development. The study concludes that while the hospital has performed well in several areas, continuous improvement guided by the Balanced Scorecard framework is essential. Future research should consider applying qualitative or mixed methods to explore the underlying causes of performance gaps and provide more comprehensive recommendations.